DNA fragility in the parallel evolution of pelvic reduction in stickleback fish - Xie, Kathleen T. (Science, 2019)
Evolution generates a remarkable breadth of living forms, but many traits evolve repeatedly, by still poorly understood mechanisms. A classic example of repeated evolution is the loss of pelvic hindfins in stickleback fish (Gasterosteus aculeatus). Repeated pelvic loss maps to recurrent deletions of a pelvic enhancer of the Pitx1 gene. Here, we identify molecular features contributing to these recurrent deletions. Pitx1 enhancer sequences form alternative DNA structures in vitro, and increase double-strand breaks and deletions in vivo. Enhancer mutability depends on DNA replication direction and is caused by (TG)-dinucleotide repeats. Modeling shows that elevated mutation rates can influence evolution under demographic conditions relevant for sticklebacks and humans. DNA fragility may thus help explain why the same loci are often used repeatedly during parallel adaptive evolution.